Anti-NMDA Receptor Encephalitis Presenting as an Acute Psychotic Episode in a Young Woman: An Underdiagnosed yet Treatable Disorder - Keller, Shikma; Roitman, Pablo; Ben-Hur, Tamir; Bonne, Omer; Lotan, Amit (Case Reports in Psychiatry, 2014)
Anti-NMDA receptor (NMDAR) encephalitis is a recently identified autoimmune disorder with prominent psychiatric symptoms. Patients usually present with acute behavioral change, psychosis, catatonic symptoms, memory deficits, seizures, dyskinesias, and autonomic instability. In female patients an ovarian teratoma is often identified. We describe a 32-year-old woman who presented with acute psychosis. Shortly after admission, she developed generalized seizures and deteriorated into a catatonic state. Although ancillary tests including MRI, electroencephalogram, and cerebrospinal fluid (CSF) analysis were unremarkable, the presentation of acute psychosis in combination with recurrent seizures and a relentless course suggested autoimmune encephalitis. The patient underwent pelvic ultrasound which disclosed a dermoid cyst and which led to an urgent cystectomy. Plasmapheresis was then initiated, yielding partial response over the next two weeks. Following the detection of high titers of anti-NMDAR antibodies in the CSF, the patient ultimately received second line immunosuppressive treatment with rituximab. Over several months of cognitive rehabilitation a profound improvement was eventually noted, although minor anterograde memory deficits remained. In this report we call for attention to the inclusion of anti-NMDAR encephalitis in the differential diagnosis of acute psychosis. Prompt diagnosis is critical as early immunotherapy and tumor removal could dramatically affect outcomes.